TINJAUAN PROGRAM PEMBINAAN PRESTASI ATLET FUTSAL CLUB SMA NEGERI 1 PERANAP - Fauzi, Yozan Alfajri; Vai, Aref; Aspa, Agus Prima (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2024)
Abstract: The purpose of this research is to find out an overview of the Achievement Development Program for Futsal Club Athletes at SMA Negeri 1 Peranap. This research is quantitative descriptive research. In this research the author used a type of field research using a quantitative approach. This research was carried out at the Garuda Football Field, Peranap District, Indragiri Hulu Regency, Riau Province, from June 2024 to September 2024. In this research, the population was 12 athletes from the SMA N 1 Peranap futsal club. Data from observations and interviews are explained in writing according to the problems discussed and accompanied by other supporting documents so that the final results of this research can be easily understood. Based on the results of research conducted regarding the Overview of the Achievement Development Program for Futsal Club Athletes at SMA Negeri 1 Peranap, it can be concluded that the implementation of the achievement training program has generally gone well. This is shown by respondents' assessments of policies, planning and resources, which are mostly in the